1949
DOI: 10.1085/jgp.32.5.579
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Bacterial Viruses in Solutions of Salts

Abstract: Burnet and McKie (1) in 1930 published a report on balanced salt action as manifested in bacteriophage phenomena. They found that coli and staphylococcal bacteriophages when diluted in 0.1 N solutions of sodium, potassiam, and ammonium salts were much more susceptible to the inactivating effects of temperature (60°C.) than were the same phages diluted in broth. The addition of a small amount of calcium, magnesium, or barium salt partially or completely prevented this inactivation. They interpreted this phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

1951
1951
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 5 publications
4
40
0
Order By: Relevance
“…Mitochondria ( 15) bacteriophages ( 1,13,16) and bacterial protoplasts (11,12,15) are damaged in the al)sence of cations, and protected from damage when cations are present. In these other systems monovalent ions (lo not seem to be effective, and often spermine and sperimidine are unusually effective protective agents.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria ( 15) bacteriophages ( 1,13,16) and bacterial protoplasts (11,12,15) are damaged in the al)sence of cations, and protected from damage when cations are present. In these other systems monovalent ions (lo not seem to be effective, and often spermine and sperimidine are unusually effective protective agents.…”
Section: Resultsmentioning
confidence: 99%
“…Adams (1949) found that the inactivation of bacteriophage by heat was exponential, and increased very rapidly over the 10" range from 63" to 73'. Bronson and Scott & Lauffer (1946) were unable to show that influenza virus haemagglutinin was destroyed as a first-order reaction when heated.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors (Burnet & McKie, 1930;Adams, 1949;Lark & Adams, 1953;Northrop, 1955) have shown that the heat stability of bacteriophage suspensions depends on the concentrations of cations in the suspending fluids. Stability was generally increased when small concentrations of divalent cations were added to a basic concentration of monovalent cation, although monovalent cations by themselves conferred less protection than distilled water (Burnet & McKie, 1930).…”
Section: Discussionmentioning
confidence: 99%